Comparison of Thermoelectric Properties of ZnO and ZnSnO Thin Films Grown on Si Substrate by Thermal Evaporation - Rehman, U.; Mahmood, K.; Ali, A.; Ikram, S. (Journal of Materials and Physical Sciences, 2020)
In this manuscript, we compared the thermoelectric properties of ZnO and ZnSnO thin films grown on silicon (100) substrate. We have evaporated Zn and Sn+Zn metal powders were evaporated in vacuum tube furnace alternatively, under same experimental conditions for the growth of ZnO and ZTO respectively. After the deposition, these grown films were cut into pieces and post growth annealed at different annealing temperatures from 600oC to 800oC in the air using programmable muffle furnace. Seebeck and Hall data suggested that ZTO sample shows highest value of Seebeck coefficient, electrical conductivity and power factor as compared to the ZnO samples. It is also observed that the value of Seebeck coefficient showing an increasing trend for both of the samples as we increase the post growth annealing temperature. The higher thermoelectric properties for ZTO are due the presence of Sn atoms in ZnO structure. Tin dopants may generate secondary phases and/or enhanced the carrier mobility which might be the reason that ZTO has improved thermo-electric properties as compared to ZnO. XRD and Raman measurements were used to confirm the formation of ZTO. XRD data verified the hexagonal structure of ZnO but a slight red shift is observed for the case of ZTO samples. To further justify our argument, we have also performed Raman spectroscopy measurements which confirmed the presence of Sn elements in ZTO.